Beginning of a new phase of the dissemination of the kilogram. (12th April 2021) - Davidson, S; Stock, M
Abstract: Following the completion of the first key comparison of realizations of the kilogram, CCM.M-K8.2019, the internationally coordinated dissemination of the kilogram has entered into a new phase on 1 February 2021. The traceability of the mass unit to the Planck constant will now be taken from the 'consensus value' of the kilogram. This letter provides the background on the phases of the dissemination of the kilogram and describes the determination of the consensus value and its consequences for mass traceability.